The Modeling and Simulation of Non-Isolated DC–DC Converters for Optimizing Photovoltaic Systems Applied in Positive Energy Districts - Tohid Hashemi; Hamed Jafari Kaleybar (Designs)
DC–DC converters are critical for energy management in positive energy districts (PEDs) because they allow for efficient conversion between different voltage levels, enabling the integration of various renewable energy sources, energy storage systems, and loads. The demand for high-voltage gain DC–DC converters in photovoltaic power systems has surged in recent times. Despite the numerous converter topologies reported, there is a focused effort to streamline components, particularly switching devices, passive elements, and overall converter losses. This paper introduces the single switching impedance network (SSIN)-based converter as a unique DC–DC converter topology, designed in both one-stage and double-stage configurations for photovoltaic applications. One of the main characteristics of the SSIN converter is that it needs just one switch and three capacitors for the n-stage. A comparative analysis with conventional boost converter topology demonstrates the SSIN-based converter’s capability to achieve a desirable output voltage that closely approximates an ideal sine waveform. Furthermore, the application of advanced control strategies to the proposed converter highlights its superior performance and robustness in maintaining output voltage stability under varying conditions. These characteristics make the SSIN-based converter particularly well-suited for PED applications, where efficiency, reliability, and the seamless integration of renewable energy sources are crucial.